FESTIVAL BUANG JONG SEBAGAI KEARIFAN LOKAL DAN MODAL SOSIAL DALAM INTEGRASI ANTARA SUKU SAWANG DAN PENDUDUK ASLI DI KABUPATEN BELITUNG - Diana, Nani; Kafarisa, Rosda Fajri (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Belitung Regency, which is administratively located within the province of Bangka Belitung, holds its own uniqueness. This writing aims in addition to know the life of the tribe of the sea (tribe sawang) in Belitung, also understand the forms of local wisdom that can integrate between the tribe of sawang and indigenous people in the area. Data analysis in this research is done through qualitative descriptive approach. Data collection techniques include observation, participatory, interview, and documentation. The result of the research shows that the close relationship between fellow tribe and tribe of sawang and indigenous people in Belitung can not be separated from historical factor and cultural activity which often done and facilitated by local government always giving place for tribe of sea . Keywords - Integration, Local Wisdom, Multiculturalism, Ethnicity